EDITORIAL EXPLOSION - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica)
In the last ten years, we experienced a real editorial explosion offered by the composer, the professor, the musicologist and the plastic artist, which is Eduard Terényi. As a creator who is both aware and careful, the author makes sure his Omnia creation will last by editing and publishing it.